Inventory And Characterization natural Orchid in Riam Nyalo, Ongkol Padang village, Landak District - Julius Serendifity; Chairani Siregar; Ahmad Mulyadi (Jurnal Sains Pertanian Equator, 2013)
Inventory and Characterization of natural Orchid is an activity in order to assess whether or not the existence of orchids and identify important traits of high economic value or which is the identifier of orchids. Characterization activity on orchids do with character, stem, leaves, flowers, and roots that include shape, texture, color and size. Quantitative characters observed were the size of stems, leaves, flowers. Qualitative characters include color, texture and shape of the stem, leaves and flowers. Orchid is a very potential biological plant. Flower, nicknamed the wilderness germ is the most diverse flowering plants, good color and shape. The diversity of orchids that are in West Kalimantan gradually become extinct and scarcity of some species. Rescue effrts to is necessary. The aim of this study was determine the species and characterization of Natural orchid contained in the Riam Nyalo Ongkol Padang village, Landak District the method be used are be by exploring the whole region of 30 hectares, and puposive sampling technique. The Result found 18 species natural orchid. Keywords: Inventory; Characterization; Natural Orchid; Landak District